Improving regioselectivity of phenylalanine aminomutase from Taxus chinensis by semi-rational mutagenesis for the biocatalytic amination of cinnamates - Tang, Tao; Wang, Miao; Zhang, Yunyun; Chen, Yijun (Frontiers in Bioengineering and Biotechnology, 2024)
The occupancy of binding pocket by the substrate ultimately determines the outcome of enzyme catalysis. Previous engineering and substrate scope of phenylalanine aminomutase from Taxus chinensis (TcPAM) has generated valuable knowledge on the regioselectivity with biocatalytic potentials for the preparation of α-and β-phenylalanine and their derivatives. However, the dramatically different regioselectivity during the amination of cinnamates by TcPAM is not fully understood. Here, we take a reconstruction approach to change the whole binding pocket of TcPAM for probing the factors affecting the regioselectivity, resulting in variant C107S/Q319M/I431V reaching 25.5-fold enhancement of β/α product ratio toward trans-cinnamate acid. Furthermore, when substituted cinnamates were used as substrates, the regioselectivity was strongly correlated with various changes of the binding pocket, and value-added 2-Cl-α-Phe (100% α-selectivity) and 4-CH3-β-Phe (98% β-selectivity) were individually verified by the mutants of L104A and Q319M at preparative scale, exemplifying the application feasibility of our engineering strategy. The present study has uncovered the cooperative connection between aromatic-binding and carboxylate-binding to affect the regioselectivity, which provides new insights into the determinants of the regioselectivity possessed by TcPAM and paves the way for its biocatalytic applications on phenylalanine derivatives.